New Results From Galileo's First Flyby of Ganymede: Reconnection‐Driven Flows at the Low‐Latitude Magnetopause Boundary, Crossing the Cusp, and Icy Ionospheric Escape - Glyn Collinson; William R. Paterson; Christopher Bard; John Dorelli; Alex Glocer; Menelaos Sarantos; Rob Wilson (Geophysical Research Letters)
Abstract On 27 June 1996, the NASA Galileo spacecraft made humanity's first flyby of Jupiter's largest moon, Ganymede, discovering that it is the only moon known to possess an internally generated magnetic field. Resurrecting the original Galileo Plasma Subsystem (PLS) data analysis software, we processed the raw PLS data from G01 and for the first time present the properties of plasmas encountered. Entry into the magnetosphere of Ganymede occurred near the confluence of the magnetopause and plasma sheet. Reconnection‐driven plasma flows were observed (consistent with an Earth‐like Dungey cycle), which may be a result of reconnection in the plasma sheet, magnetopause, or might be Ganymede's equivalent of a Low‐Latitude Boundary Layer. Dropouts in plasma density combined with velocity perturbations afterward suggest that Galileo briefly crossed the cusps into closed magnetic field lines. Galileo then crossed the cusps, where field‐aligned precipitating ions were observed flowing down into the surface, at a location consistent with observations by the Hubble Space Telescope. The density of plasma outflowing from Ganymede jumped an order of magnitude around closest approach over the north polar cap. The abrupt increase may be a result of crossing the cusp or may represent an altitude‐dependent boundary such as an ionopause. More diffuse, warmer field‐aligned outflows were observed in the lobes. Fluxes of particles near the moon on the nightside were significantly lower than on the dayside, possibly resulting from a diurnal cycle of the ionosphere and/or neutral atmosphere.